Cost-effectiveness of neonatal surgery for congenital anomalies in low-income and middle-income countries: a systematic review protocol. Issue 1 (30th August 2020) - Kim, Na Eun; Vervoot, Dominique; Hammouri, Ahmad; Riboni, Cristiana; Salem, Hosni; Grimes, Caris; Wright, Naomi Jane
Abstract : Introduction: Congenital anomalies are the fifth leading cause of death in children under 5 years old globally (591 000 deaths reported in 2016). Over 95% of deaths occur in low-income and middle-income countries (LMICs). It is estimated that two-thirds of the congenital anomaly health burden could be averted through surgical intervention and that such interventions can be cost-effective. This systematic review aims to evaluate current evidence regarding the cost-effectiveness of neonatal surgery for congenital anomalies in LMICs. Methods and analysis: A systematic literature review will be conducted in PubMed, MEDLINE, Embase, Cochrane Library, Scielo, Google Scholar, African Journals OnLine and Regional WHO's African Index Medicus databases for articles on the cost-effectiveness of neonatal surgery for congenital anomalies in LMICs. The following search strings will be used: (1) congenital anomalies; (2) LMICs; and (3) cost-effectiveness of surgical interventions. Articles will be uploaded to Covidence software, duplicates removed and the remaining articles screened by two independent reviewers. Cost information for interventions or procedures will be extracted by country and condition. Outcome measurements by reported unit and cost-effectiveness ratios will be extracted. Methodological quality of each article will be assessed using the Drummond checklist for economic evaluations. The Agency for Healthcare Research and Quality's Effective Health Care Program guidance will be followed to assess the grade of the studies. Ethics and dissemination: No ethical approval is required for conducting the systematic review. There will be no direct collection of data from individuals. The finalised article will be published in a scientific journal for dissemination. The protocol has been registered with PROSPERO (International Prospective Register of Systematic Reviews). Conclusion: Congenital anomalies form a large component of the global health burden that is amenable to surgical intervention. This study will systematically review the current literature on the cost-effectiveness of neonatal surgery for congenital anomalies in LMICs. PROSPERO registration number: CRD42020172971.